2012
DOI: 10.1111/j.1365-2621.2012.02944.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of turmeric and lemongrass essential oils and their mixture on quality changes of refrigerated green mussel (Perna viridis)

Abstract: Summary Effect of turmeric and lemongrass essential oils (Eos) and their mixture on quality of green mussel stored at 4 °C was investigated. The mixture of 0.25% turmeric and 0.25% lemongrass Eos could lower microbiological and chemical deterioration of mussel as evidenced by the lower microbial counts, total volatile base, ammonia, trichloroacetic acid‐soluble peptide contents and thiobarbituric acid‐reactive substances, compared with the control (P < 0.05). It indicated that a mixture of turmeric and lemongr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
(48 reference statements)
2
16
1
1
Order By: Relevance
“…Several studies reported that combined EOs increased antimicrobial activity. The mixture of Laurus nobilis L. and Myrtus communis L. essential oils reduced more mesophilic bacteria counts compared to individual oil alone (Masniyom et al ., ). The combined Chinese cinnamon and cinnamon bark oils improved inhibitory effects against E. coli , L .…”
Section: Resultsmentioning
confidence: 97%
“…Several studies reported that combined EOs increased antimicrobial activity. The mixture of Laurus nobilis L. and Myrtus communis L. essential oils reduced more mesophilic bacteria counts compared to individual oil alone (Masniyom et al ., ). The combined Chinese cinnamon and cinnamon bark oils improved inhibitory effects against E. coli , L .…”
Section: Resultsmentioning
confidence: 97%
“…A mixture of 0.25 % turmeric and 0.25 % lemongrass EOs showed synergistic effects on the retardation of lipid oxidation of green mussel (Perna canalicula) stored at 4°C (Masniyom et al 2012). However, samples treated with 0.5 % lemongrass oil exhibited a higher likeness score for odour and flavour compared to samples treated with other EOs, making lemongrass EO the most promising agent to prevent deterioration and maintain the odour and flavour attributes of mussel during prolonged refrigerator storage.…”
Section: Seafoodmentioning
confidence: 87%
“…Furthermore, turmeric and lemongrass EOs lowered the microbial deterioration of green mussels (Perna canaliculus). The best results were obtained by applying a mixture of both EOs: 0.25 % turmeric EO and 0.25 % lemongrass EO (Masniyom et al 2012).…”
Section: Seafoodmentioning
confidence: 96%
“…The oil of this plant was used as antibacterial treatment against Salmonella Newport inoculated on green leafy vegetables, where the greatest reduction was observed in iceberg lettuce (4.3 log), followed by spinach, mature spinach, and romaine lettuce; however, in this study the sensorial effect of the treatment was not considered (Moore‐Neibel and others ). On the other hand, the mixture of C. citratus and turmeric acid applied in mussel reduced the microbial counts and retarded lipid oxidation compared to controls, additionally the C. citratus oil was found sensorially more acceptable than turmeric acid treatment to preserve the odor and flavor of foods (Masniyom and others ). The addition of lemongrass oil into gelatin film could enhance the antimicrobial and antioxidative properties of sea bass slices (Ahmad and others ).…”
Section: Premise III the Composition Of Medicinal Plants Is An Indicmentioning
confidence: 99%
“…Medicinal plant parts (roots, leaves, branches/stems, barks, flowers, and fruits) are commonly rich in terpenes (carvacrol, citral, linalool, and geraniol) and phenolics (flavonoids and phenolic acids), and these compounds have been effective as food additives (Cai and others ). For example, lemongrass is a medicinal plant utilized as stomachic, antispasmodic, carminative, and antihypertensive agent (Naik and others ); in addition, it is a source of terpenes like citral that has shown antimicrobial activity against food pathogen and deteriorative bacteria, and antioxidant effect avoiding lipid peroxidation in food matrices (Ahmad and others ; Masniyom and others ). Other medicinal plants that could be used to sustain the idea of generating extracts with potential as food additives are: Chenopodium ambrosioides rich in terpenes (used to control menses disorders, fibroids, uterine hemorrhage, and parasitic diseases); Euphorbia stenoclada rich in phenolics (used to control skin diseases, gonorrhoea, migraine, intestinal parasites and wart cures); Geranium mexicanum rich in terpenes and phenolics (used as remedy against tonsillitis, cough, whooping cough, urticaria, dysentery and diarrhea); Gnaphalium oxyphyllum rich in phenolics (used to treat gripe, fever, asthma, bronchitis, and cough); Helianthemum glomeratum rich in flavonoids (used to treat bloody and mucoid diarrheas and for the relief of abdominal pain); Larrea tridentata rich in phenolic compounds (used to treat respiratory infections as tuberculosis); Marrubium vulgare rich in terpenes and phenolics (used mainly as an expectorant); Peumus boldus rich in phenolics and alkaloids (regulator of the hepatic function, colagogue, antispasmodic, digestive stimulant, and nervous sedative); Eysenhardtia polystachya rich in flavonoids (used to treat kidney and bladder infections, diuretic, antispasmodic and febrifuge).…”
Section: Introductionmentioning
confidence: 99%